2015
DOI: 10.1128/aac.04006-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Intracellular Activities of Peptide Deformylase Inhibitor GSK1322322 against Legionella pneumophila Isolates

Abstract: b GSK1322322, a novel peptide deformylase inhibitor currently in development as an oral and intravenous agent for the treatment of hospitalized community-acquired bacterial pneumonia, showed poor in vitro activity against a panel of 50 Legionella pneumophila strains, with MICs ranging from 1 to 16 g/ml and an MIC 90 of 16 g/ml, but very potent intracellular activity, with the minimum extracellular concentrations capable of inhibiting intracellular proliferation (MIECs) ranging from 0.12 to 2 g/ml and 98% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on the advantages of broad-spectrum activity, rapid killing rate and low drug resistance, antimicrobial peptides (AMPs) open a new way for the development of antimicrobial agents ( Czaplewski et al, 2016 ). It has been demonstrated that some AMPs such as cathelicidin ( Sonawane et al, 2011 ), GSK1322322 ( Dubois et al, 2015 ), plectasin derivatives-MP1102/NZ2114/H2 ( Brinch et al, 2010 ; Wang X. et al, 2018 , 2019 ), and temporins ( Crepin et al, 2020 ) exhibit potent intracellular activity against Mycobacterium tuberculosis , Legionella pneumophila , methicillin-susceptible/-resistant Staphylococcus aureus , and Legionella pneumophila , respectively. A marine peptide-NZ17074 (N1) is a variant of arenicin-3 (Tyr5→Asn, Tyr17→His) isolated from marine lugworm Arenicola marina and has strong intracellular antibacterial activity against Gram-negative bacteria (including Escherichia coli , Salmonella , Pseudomonas aeruginosa , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Based on the advantages of broad-spectrum activity, rapid killing rate and low drug resistance, antimicrobial peptides (AMPs) open a new way for the development of antimicrobial agents ( Czaplewski et al, 2016 ). It has been demonstrated that some AMPs such as cathelicidin ( Sonawane et al, 2011 ), GSK1322322 ( Dubois et al, 2015 ), plectasin derivatives-MP1102/NZ2114/H2 ( Brinch et al, 2010 ; Wang X. et al, 2018 , 2019 ), and temporins ( Crepin et al, 2020 ) exhibit potent intracellular activity against Mycobacterium tuberculosis , Legionella pneumophila , methicillin-susceptible/-resistant Staphylococcus aureus , and Legionella pneumophila , respectively. A marine peptide-NZ17074 (N1) is a variant of arenicin-3 (Tyr5→Asn, Tyr17→His) isolated from marine lugworm Arenicola marina and has strong intracellular antibacterial activity against Gram-negative bacteria (including Escherichia coli , Salmonella , Pseudomonas aeruginosa , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Omadacycline demonstrates in vitro activity against Gram‐positive aerobes (including methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant enterococci), some Gram‐negative aerobes, many anaerobes, and atypical pathogens including Legionella spp. and Mycoplasma spp . In previous clinical studies in patients with complicated skin and skin structure infection, omadacycline treatment was started with IV administration, after which participants could transition to oral therapy (200 or 300 mg orally once daily, depending on the study) for a total of up to 14 days of treatment .…”
mentioning
confidence: 99%